Amyloid Precursor-Like Protein 2 deletion-induced retinal synaptopathy related to congenital stationary night blindness: structural, functional and molecular characteristics. Issue 1 (December 2016) - Dinet, Virginie; Ciccotosto, Giuseppe; Delaunay, Kimberley; Borras, Céline; Ranchon-Cole, Isabelle; Kostic, Corinne; Savoldelli, Michèle; El Sanharawi, Mohamed; Jonet, Laurent; Pirou, Caroline; An, Na; Abitbol, Marc; et al.
Abstract Background Amyloid precursor protein knockout mice (APP-KO) have impaired differentiation of amacrine and horizontal cells. APP is part of a gene family and its paralogue amyloid precursor-like protein 2 (APLP2) has both shared as well as distinct expression patterns to APP, including in the retina. Given the impact of APP in the retina we investigated how APLP2 expression affected the retina using APLP2 knockout mice (APLP2-KO). Results Using histology, morphometric analysis with noninvasive imaging technique and electron microscopy, we showed that APLP2-KO retina displayed abnormal formation of the outer synaptic layer, accompanied with greatly impaired photoreceptor ribbon synapses in adults. Moreover, APLP2-KO displayed a significant decease in ON-bipolar, rod bipolar and type 2 OFF-cone bipolar cells (36, 21 and 63 %, respectively). Reduction of the number of bipolar cells was accompanied with disrupted dendrites, reduced expression of metabotropic glutamate receptor 6 at the dendritic tips and alteration of axon terminals in the OFF laminae of the inner plexiform layer. In contrast, the APP-KO photoreceptor ribbon synapses and bipolar cells were intact. The APLP2-KO retina displayed numerous phenotypic similarities with the congenital stationary night blindness, a non-progressive retinal degeneration disease characterized by the loss of night vision. The pathological phenotypes in the APLP2-KO mouse correlated to altered transcription of genes involved in pre- and postsynatic structure/function, including CACNA1F, GRM6, TRMP1 and Gα0, and a normal scotopic a-wave electroretinogram amplitude, markedly reduced scotopic electroretinogram b-wave and modestly reduced photopic cone response. This confirmed the impaired function of the photoreceptor ribbon synapses and retinal bipolar cells, as is also observed in congenital stationary night blindness. Since congenital stationary night blindness present at birth, we extended our analysis to retinal differentiation and showed impaired differentiation of different bipolar cell subtypes and an altered temporal sequence of development from OFF to ON laminae in the inner plexiform layer. This was associated with the altered expression patterns of bipolar cell generation and differentiation factors, including MATH3, CHX10, VSX1 and OTX2. Conclusions These findings demonstrate that APLP2 couples retina development and synaptic genes and present the first evidence that APLP2 expression may be linked to synaptic disease.